Determinants of choice of credit source among clients of microfinance systems in the Upper West Region of Ghana - Paul Bata Domanban; Fauster Agbenyo; Samuel Sekyi (Cogent Business & Management, 2023)
Microfinance institutions must understand what influences their clients' choice of credit source in order to design and provide adequate and appropriate credit facilities to their clients. This paper explores the determinants of the choice of credit source among beneficiaries of microfinance systems in the Upper West Region of Ghana. An interview guide and a questionnaire were used to collect data. The study employed the multinomial probit model to analyse the data. The study revealed that gender, arable crop farming, household size, dependency ratio, access to microfinance information, repayment period, group size, interest rate, distance, loan amount, borrowing experience, household assets, and household members employed were the main determinants of the choice of credit source among beneficiaries. The study recommends that the Bank of Ghana, through the Apex Bank, standardise repayment periods and procedures such that banks compete on innovative methods of sourcing borrowers, which could result in efficiency in the lending industry.
Keywords: 650; choice of credit source; Ghana; microfinance systems; multinomial probit model; upper west region